Upper extremity reconstruction following open surgical repair of giant arteriovenous fistula aneurysm: clinical case and systematic review of the literature - Almerey, Tariq A; Oliver, Jeremie D; Jorgensen, Matthew S; Rinker, Brian D; Farres, Houssam A; Hakaim, Albert G; Forte, Antonio Jorge (Acta Biomedica Atenei Parmensis, 2020)
Background: Nearly 30% of arteriovenous fistulas (AVFs) located in the upper extremity for hemodialysis access result in short- and long-term adverse effects, such as rupture, necessitating emergent surgical management and extensive soft-tissue reconstruction. With this systematic review, we aimed to compile all reported open surgical techniques used for complicated AVF repair in the upper extremity, the respective soft-tissue reconstructive outcomes, and vascular patency rates at final follow-up.Methods: Using Ovid Medline/PubMed databases, we conducted a review of the English-language literature on AVF aneurysm surgical management in the upper extremity, filtered for relevance to open surgical technique and outcomes in vascular patency after aneurysmal repair at long-term follow-up (≥6 months postoperatively). We include a detailed case of surgical removal of a giant AVF aneurysm and subsequent flap elevation and reconstruction of the upper extremity.Results: Of 150 articles found in the initial search, 19 (from 2010-2017) met inclusion criteria. From the reviewed studies, 675 patients underwent open surgical repair of AVF aneurysm in the upper extremity. Surgical approaches included partial-to-full aneurysm excision, interposition graft, tubularized extracellular matrix, sutured and stapled aneurysmorrhaphy, and stent graft. Rates of vascular patency at repair site ranged from 47% to 100%, with a pooled average of 78% at 6 months or longer postoperatively.Conclusions: For plastic and hand surgeons, aneurysmal ligation and excision is feasible even in severe cases and is associated with overall good vascular and soft-tissue reconstructive outcomes in the upper extremity.Level of Evidence: III